Synthesis, anticancer, structural, and computational docking studies of 3-benzylchroman-4-one derivatives. Issue 23 (1st December 2017) - Simon, Lalitha; Abdul Salam, Abdul Ajees; Madan Kumar, S.; Shilpa, T.; Srinivasan, K.K.; Byrappa, K.
Graphical abstract: Abstract: A series of 3-Benzylchroman-4-ones were synthesized and screened for anticancer activity by MTT assay. The compounds were evaluated against two cancerous cell lines BT549 (human breast carcinoma), HeLa (human cervical carcinoma), and one noncancerous cell line vero (normal kidney epithelial cells).3b was found to be the most active molecule against BT549 cells (IC50  = 20.1 µM) and3h against HeLa cells (IC50  = 20.45 µM).3b also exhibited moderate activity against HeLa cells (IC50  = 42.8 µM). The molecular structures of3h and3i were solved by single crystal X-ray crystallographic technique. Additionally, the molecular docking studies between the tumour suppressor protein p53 with the lead compound3h, which exhibited better anticancer activity against HeLa cells was examined.